Indah Mawarni& Syilvia Desi Septiana, PENGARUH KOMUNIKASI ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJAKARYAWAN PADA PT.BANK BUKOPIN, Tbk. CABANG PALEMBANG - Indah Mawarni; Syilvia Dewi Septiana (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determinethe effect of organizational communication on the performance of employees, the effect of work motivation on the performance of employees and the influence of organizational communication, and work motivation on the performance of employees of PT. Bank Bukopin, Tbk. Palembang Branch both partially and simultaneously.The sample used in this study was a permanent employee of PT. Bank Bukopin, Tbk. Palembang Branch, which has a minimum service period of 2 years and has offices in Palembang Main Branch as many as 30 respondents. The technique used in taking this sample is to use one of the non probability sampling techniques, namely purposive sampling. The analytical method used is descriPT.ive analysis method using path analysis with the SPSS for Windows version 23.The test results of the hypothesis indicate that the variables: (1) organizational communication has a positive effect on employee performance. (2) Work Motivation of Organizational Communication and Work Motivation means that work motivation has a positive and significant effect on employee performance. (3) Organizational Communication and Work Motivation have a positive effect on Employee Performance at PT.Bank Bukopin, Tbk. Palembang Branch. Organizational communication and work motivation together have an effect on employee performance.